2016
DOI: 10.1177/1078155216679026
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on the barriers associated with medication adherence to oral chemotherapy

Abstract: Purpose Appropriate use of oral chemotherapy is a challenge for patients and clinicians. The purpose of this study was to analyze cancer patients' use of oral chemotherapies and identify opportunities to improve adherence. Methods We developed a 30-question survey to address frequency and reasons for reducing/skipping doses; sources of information for oral chemotherapy use; perceived importance of food-drug effects; and ease of understanding labeling directions. Results Ninety-three patients taking oral chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…The result implies education enhances individual knowledge in social, economical and health related cases and those educated individuals may be keeping them from chewing khat. This is in line with the finding of Muluneh et al (2018) who revealed that integrate education of the potential health problems of khat chewing is important to reduce the number of chewers.…”
Section: Educational Levels Of Respondentsupporting
confidence: 90%
See 2 more Smart Citations
“…The result implies education enhances individual knowledge in social, economical and health related cases and those educated individuals may be keeping them from chewing khat. This is in line with the finding of Muluneh et al (2018) who revealed that integrate education of the potential health problems of khat chewing is important to reduce the number of chewers.…”
Section: Educational Levels Of Respondentsupporting
confidence: 90%
“…Furthermore, chewing of khat has serious socioeconomic effect on households' income to fulfill nutritious food, home improvement, education or other family needs and finally leads to financial problem and family breakdown. It also affects working hours, causes absenteeism from work, absenteeism from class and poor academic performance of the students and unemployment (Amsalu et al, 2017;Beyene et al, 2017;Ng'ethe, 2015;Muluneh, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous studies, forgetfulness was the most frequently cited reason for nonadherence. 3,7,13,40 Responses also provided insights into AYA lifestyle factors that could guide future intervention, including reports of being away from home when medication doses were missed. Interventions could help AYAs develop proactive plans for medication-taking for times that they are away from home or out of their usual routine.…”
Section: Discussionmentioning
confidence: 99%
“…Other team members, such as clinical oncology pharmacists and seasoned clinical nursing staff, should be integrated into the care team to support communication of personalized treatment plans, dosing schedules, FDA labeling instructions, expected side effect profiles, and management of side effects. 2 Similarly, other team members, such as social workers, can help in other QoL domains. Regular evaluation of a patient's social support is vital to identify deficiencies that may require additional measures, such as more frequent check-ins or assistance with transportation.…”
mentioning
confidence: 99%